2017
DOI: 10.1002/adma.201700001
|View full text |Cite
|
Sign up to set email alerts
|

Amorphizing of Au Nanoparticles by CeOx–RGO Hybrid Support towards Highly Efficient Electrocatalyst for N2 Reduction under Ambient Conditions

Abstract: Ammonia synthesis is one of the most kinetically complex and energetically challenging chemical processes in industry and has used the Harber-Bosch catalyst for over a century, which is processed under both harsh pressure (150-350 atm) and hightemperature (623-823 K), wherein the energy and capital intensive Harber-Bosch process has a huge energy cost accounting for about 1%-3% of human's energy consumption. Therefore, there has been a rough and vigorous exploration to find an environmentally benign alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
381
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 545 publications
(402 citation statements)
references
References 36 publications
8
381
1
Order By: Relevance
“…This outstanding performance in as-obtained noblemetal-free catalyst is even comparable with the yield of N 2 fixation under harsh temperatures and/or pressures (Supporting Information, Table S1). [30,47] As exhibited in Figure 3b and the Supporting Information, Figure S20, no obvious fluctuation arises in the average yields and the current intensities,i mplying asobtained nanostructured BVC-A can guarantee the stability during the catalytic process. The corresponding detection calibration curves are shown in the Supporting Information, Figure S16, S17.…”
Section: Angewandte Chemiementioning
confidence: 74%
See 2 more Smart Citations
“…This outstanding performance in as-obtained noblemetal-free catalyst is even comparable with the yield of N 2 fixation under harsh temperatures and/or pressures (Supporting Information, Table S1). [30,47] As exhibited in Figure 3b and the Supporting Information, Figure S20, no obvious fluctuation arises in the average yields and the current intensities,i mplying asobtained nanostructured BVC-A can guarantee the stability during the catalytic process. The corresponding detection calibration curves are shown in the Supporting Information, Figure S16, S17.…”
Section: Angewandte Chemiementioning
confidence: 74%
“…Asomewhat broader and weaker Raman-active mode accompanied with obvious Raman-band shifts elucidate that the local lattice imperfections,t he maintenance of short-range order,a sw ell as distorted lattices with variations in bonding length and angle arise together in amorphous Bi 4 V 2 O 11 (Figure 2d; Supporting Information, Figure S5). [30] Along with the benefits of amorphization, introducing CeO 2 will establish band alignment with amorphous Bi 4 V 2 O 11 , which might also be conductive to electrocatalytic NRR. [30] Along with the benefits of amorphization, introducing CeO 2 will establish band alignment with amorphous Bi 4 V 2 O 11 , which might also be conductive to electrocatalytic NRR.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…In N 2 -fixing bacteria, nitrogenases biologically can catalyze the reduction of N 2 to NH 3 at ambient conditions. [6,[9][10][11] This traditional process is not only energy-intensive, but the H 2 used as the feeding gas often comes from fossil fuels leading to serious greenhouse gas emission. [6,[9][10][11] This traditional process is not only energy-intensive, but the H 2 used as the feeding gas often comes from fossil fuels leading to serious greenhouse gas emission.…”
mentioning
confidence: 99%
“…Alternatively, multiple encouraging strategies, including photocatalysis, mimicking biological nitrogen, and electrocatalysis were gradually developed to realize artificial N 2 fixation at mild conditions. Up to now, although a number of electrocatalysts were investigated, including the metals, [8][9][10][11] the metal oxide or sulfide, [12][13][14] and metal-free compounds, [15][16][17] there are still many shortcomings. [6] It has been extensively reported that heterogenous catalysts play vital roles in breaking or lowing the energy barrier required in the rate-determining step in electroreduction from N 2 to NH 3 , [7] which is the key in further improving N 2 reduction reaction (NRR) performances.…”
mentioning
confidence: 99%